2006
DOI: 10.1073/pnas.0607040103
|View full text |Cite
|
Sign up to set email alerts
|

Compartmental signal modulation: Endosomal phosphatidylinositol 3-phosphate controls endosome morphology and selective cargo sorting

Abstract: It is increasingly recognized that the compartmental organization of signaling processes has a profound influence on cellular behavior. However, our inability to influence these compartmental events in a spatially restricted and acute manner limits our understanding of causation. To determine whether local compartmental loss of a phosphoinositide disrupts the normal traffic of specific cargoes through endosomes, we developed the use of a regulated dimerization device, here designed to compartmentally modify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 27 publications
7
78
0
Order By: Relevance
“…Recruitment and PI turnover is thought to be regulated by Vps34 ( Figure 4) (Cao, Laporte et al 2007) and by the phosphatase-inactive MTMR12 (Nandurkar, Layton et al 2003). Targeted recruitment of MTM1 to early endosomes and thereby PI(3)P depletion enhances microtubule-dependent endosome tubulation (Fili, Calleja et al 2006) during endosomal recycling. However, based on other studies local PI(3)P-turnover was suggested to be a crucial determinant for tubule formation (Carpentier, N'Kuli et al 2013).…”
Section: Mtm1 Regulates Endosomal Pi(3)p Turnover and Membrane Dynamicsmentioning
confidence: 99%
“…Recruitment and PI turnover is thought to be regulated by Vps34 ( Figure 4) (Cao, Laporte et al 2007) and by the phosphatase-inactive MTMR12 (Nandurkar, Layton et al 2003). Targeted recruitment of MTM1 to early endosomes and thereby PI(3)P depletion enhances microtubule-dependent endosome tubulation (Fili, Calleja et al 2006) during endosomal recycling. However, based on other studies local PI(3)P-turnover was suggested to be a crucial determinant for tubule formation (Carpentier, N'Kuli et al 2013).…”
Section: Mtm1 Regulates Endosomal Pi(3)p Turnover and Membrane Dynamicsmentioning
confidence: 99%
“…Currently, altering cellular PI(4,5)P 2 levels requires the use of chemical dimerizers (40)(41)(42)(43), biological lipid recognition domains or lipid metabolizing enzymes, which are prone to interference by protein-protein interactions. In addition, response times are subject to biological restrains, since the cell has to express sufficient amounts of protein prior to any observable effects.…”
Section: Phdm Decreases the Amount Of Mitochondriamentioning
confidence: 99%
“…Plasmids used as templates containing the tandem FK506-binding protein domain (2xFKBP) and the mutant FRB domain (FRB*) were previously constructed from components of the ARGENT Regulated Heterodimerization Kit provided by ARIAD (Fili et al, 2006). To generate the target fusion constructs, EGFP-2xFKBP was amplified by standard PCR using the GFP-Rab5a-target plasmid as template and the product subcloned into AgeI-BamHI sites of pIRESpuro2 (Clonetech).…”
Section: Plasmid Construction Sirna and Transfectionmentioning
confidence: 99%
“…To address the question of what is sufficient to suppress the aPKC dependence of signal delivery, under conditions where aPKC function is blocked, we have triggered delivery independently using the dimerization agent rapalogue (Fili et al, 2006;Inoue et al, 2005;Varnai et al, 2006). Exploiting this approach we show that the localized activation of ERK at the leading edge and not the related JNK can indeed partially rescue the loss of aPKC action, restoring focal adhesion dynamics.…”
Section: Introductionmentioning
confidence: 99%